Does exercise intensity matter for fatigue during (neo‐)adjuvant cancer treatment? The Phys‐Can randomized clinical trial. (2nd March 2021) - Demmelmaier, Ingrid; Brooke, Hannah L.; Henriksson, Anna; Mazzoni, Anne‐Sophie; Bjørke, Ann Christin Helgesen; Igelström, Helena; Ax, Anna‐Karin; Sjövall, Katarina; Hellbom, Maria; Pingel, Ronnie; Lindman, Henrik; Johansson, Silvia; et al.
Abstract: Exercise during cancer treatment improves cancer‐related fatigue (CRF), but the importance of exercise intensity for CRF is unclear. We compared the effects of high‐ vs low‐to‐moderate‐intensity exercise with or without additional behavior change support (BCS) on CRF in patients undergoing (neo‐)adjuvant cancer treatment. This was a multicenter, 2x2 factorial design randomized controlled trial (Clinical Trials NCT02473003) in Sweden. Participants recently diagnosed with breast (n = 457), prostate (n = 97) or colorectal (n = 23) cancer undergoing (neo‐)adjuvant treatment were randomized to high intensity (n = 144), low‐to‐moderate intensity (n = 144), high intensity with BCS (n = 144) or low‐to‐moderate intensity with BCS (n = 145). The 6‐month exercise intervention included supervised resistance training and home‐based endurance training. CRF was assessed by Multidimensional Fatigue Inventory (MFI, five subscales score range 4‐20), and Functional Assessment of Chronic Illness Therapy‐Fatigue scale (FACIT‐F, score range 0‐52). Multiple linear regression for main factorial effects was performed according to intention‐to‐treat, with post‐intervention CRF as primary endpoint. Overall, 577 participants (mean age 58.7 years) were randomized. Participants randomized to high‐ vs low‐to‐moderate‐intensity exercise had lower physical fatigue (MFI Physical Fatigue subscale; mean difference −1.05 [95% CI: −1.85, −0.25]), but the difference was not clinically important (ie <2). We found no differences in other CRF dimensions and no effect of additional BCS. There were few minor adverse events. For CRF, patients undergoing (neo‐)adjuvant treatment for breast, prostate or colorectal cancer can safely exercise at high‐ or low‐to‐moderate intensity, according to their own preferences. Additional BCS does not provide extra benefit for CRF in supervised, well‐controlled exercise interventions.